Pengaruh Content Marketing, Electronic Word Of Mouth, dan User Generated Content Terhadap Keputusan Pembelian Produk Shopee Pada Mahasiswa Pendidikan Ekonomi Angkatan 2019-2021 - Nurlaili Nanda Riyanti; Jonet Ariyanto Nugroho; Dini Octoria (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2025)
This research aims to determine the influence of content marketing, electronic word of mouth, and user generated content on purchasing decisions for Shopee products among Economics Education students at FKIP UNS class of 2019-2021. This research used quantitative descriptive methods. The sample collection used a purposive sampling technique with a total sample of 97 students. Data collection was obtained through a questionnaire filled in by FKIP UNS Economics Education students class of 2019-2021 who had purchased products on Shopee. The data analysis technique used multiple linear regression analysis with the help of SPSS 25 for Windows software. The results of the research showed that (1) there was a positive and significant influence between content marketing on purchasing decisions for Shopee products among FKIP UNS Economics Education students class of 2019-2021(2) there was a positive and significant influence between electronic word of mouth on purchasing decisions for Shopee products among Economics Education students at FKIP UNS class of 2019-2021(3) there was a positive and significant influence between user generated content on purchasing decisions for Shopee products among FKIP Economics Education students UNS class of 2019-2021 (4) there was a positive and significant influence between content marketing, electronic word of mouth and user generated content on purchasing decisions for Shopee products among Economics Education students FKIP UNS class of 2019-2021.